PENGARUH ABDOMINAL STRETCHING EXERCISE TERHADAP PENURUNAN NYERI DYSMENORRHOEA (Politeknik Kesehatan Kemenkes Bandung, 2022)
Reproductive health is physical, mental and social well-being as a whole in all matters relating to the reproductive system and function, as well as the reproductive process and not just a condition that is free from disease and disability1. Menstrual pain is a feeling of discomfort that arises from the female reproductive system during menstruation1. Dysmenorrhea occurs in the lower abdomen before menstruation or during menstruation due to uterine muscle contractions. Symptoms of dysmenorrhea often occur on the first or second day of menstruation2. This evidence based case report aims to identify the effect of Abdominal Stretching Exercise on reducing dysmenorrhoea pain. The search for articles regarding the effect of Abdominal Stretching Exercise on reducing dysmenorrhea pain was carried out on the Garuda e-data based, so that 3 articles were obtained with Pre-Experimental and Quasi-Experimental research designs and met the inclusion criteria that had been previously determined, then a journal review was conducted, and it was found that Abdominal Stretching Exercise affects the reduction of dysmenorrhea pain and can be applied to patients.